INDEPENDENT EDUCATION AND THE IMPORTANCE OF FLOUR - Niyazova, Gulnoraxon (MMIT Proceedings, 2023)
This article will reflect and reflect on the issues of how students' involvement in sustainable education can help improve learning strategies and increase their activity, which will appeal to teachers